2021
DOI: 10.3390/jmse10010038
|View full text |Cite
|
Sign up to set email alerts
|

Fish Composition and Diversity of Four Coral Reefs in the South China Sea Based on Hand-Line Catch

Abstract: To improve the overall understanding of the fish diversity and spatial patterns of major coral reefs in the South China Sea, fish assemblage composition, dominant species, biodiversity indices, and multivariate analysis of community structure were reported for four major coral reefs based on hand-line survey data in May and September 2018. A total of five orders, 21 families, 45 genera and 121 species of fish were recorded with Perciformes (78.5%) being the most diverse. The highest number (5) of dominant spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Therefore, it could be speculated that the coral reef area in China is the main activity area of coral reef fishes between the Indian and Pacific Oceans. According to the "Island Effect" theory, coral reef species diversity is closely related to coral reef cover area, a well-known concept in coral reef ecology [30]. The total area of coral reefs in the South China Sea is approximately 3 × 10 4 km 2 , accounting for 5% of the global coral reef area (60 × 10 4 km 2 ) [28,47].…”
Section: Coral Reef Fish Species Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it could be speculated that the coral reef area in China is the main activity area of coral reef fishes between the Indian and Pacific Oceans. According to the "Island Effect" theory, coral reef species diversity is closely related to coral reef cover area, a well-known concept in coral reef ecology [30]. The total area of coral reefs in the South China Sea is approximately 3 × 10 4 km 2 , accounting for 5% of the global coral reef area (60 × 10 4 km 2 ) [28,47].…”
Section: Coral Reef Fish Species Compositionmentioning
confidence: 99%
“…This may be because the coral reefs in China are located on the northern edge of the "coral triangle" with low latitude and high temperature and affected by the cold flow of the mainland's estuary and the South China Sea tropical warm currents, forming a unique coral reef ecosystem that integrates multiple physical, chemical, geological, energy, and material flow properties [28]. Many studies have shown that the composition of coral reef fishes is closely related to the status of coral reefs, human interference, environmental factors, and sampling time and methods [27,30,[51][52][53].…”
Section: Coral Reef Fish Species Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…rising ocean temperature and unsustainable fishing (Allgeier et al, 2016;Hughes et al, 2017;Munday et al, 2008). The South China Sea (SCS) is a globally significant area because of its shallow coral reefs and high biodiversity (Chen and Li, 2005;Arai, 2015;Lu et al, 2021;Dai et al, 2022;Li et al, 2022). Under multiple stressors of human activities and climate change, the coral cover in the SCS has severely declined within the past few decades, and coral reef fish populations have receded (Hughes et al, 2013;Zhao et al, 2013;Zhao et al, 2016;Hughes et al, 2017;Zhang et al, 2021a;Zhang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%